Extended Abstracts Publication of the Annual Symposium on Computer-Human Interaction in Play 2017
DOI: 10.1145/3130859.3131319
|View full text |Cite
|
Sign up to set email alerts
|

Productivity & Play

Abstract: Building 3D scenes for games can be a difficult task, especially for beginners and other non-experts wanting to contribute their own ideas in an easy way. Tools for map or world creation are often complex to understand and use, don't support the creative process of building a scene, and decouple design from player experience. To overcome these problems, we present a First-Person Shooter (FPS) game for level creation using game mechanics for all tasks, making the process more easy and enjoyable while also provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Additionally, we found that hedonistic and, interestingly, also the pragmatic quality of the game is rated higher than for the editor. This came as a surprise since the editor is highly task oriented and pragmatic in its design, functionality, and user experience [42].…”
Section: Playful Shooter For Fast and Easy Scene Designmentioning
confidence: 99%
“…Additionally, we found that hedonistic and, interestingly, also the pragmatic quality of the game is rated higher than for the editor. This came as a surprise since the editor is highly task oriented and pragmatic in its design, functionality, and user experience [42].…”
Section: Playful Shooter For Fast and Easy Scene Designmentioning
confidence: 99%